AB1043 The clinical profile of gout significantly differs between male and female. (12th June 2018) - te Kampe, R.; van Durme, C.; Janssen, M.; Boonen, A.; Jansen, T.
Abstract : Background: Gout, the most common type of inflammatory arthritis, is considered as a predominant male disease. Notwithstanding, there is an increased risk of gout in female after the menopause. Objectives: Our objective was to assess differences in the clinical features between female and male patients. Methods: Data of newly diagnosed gout patients attending the rheumatology outpatient clinics of one secondary and one tertiary i.e. university centre in the south of the Netherlands were used. We compared baseline characteristics of males and females regarding to demographics, BMI, presence of tophi, medication use (diuretics, prophylaxis of gout and uric acid lowering drugs), serum and urine concentration of uric acid and creatinine, and comorbidities. Additional, fractional excretion of uric acid (FEUa), calculated as (urinary uric acid x serum creatinine)/(serum uric acid x urinary creatinine), was compared. FEUa gives the percentage of uric acid renally filtered and thus excreted in the urine (normal range 7%–12%). Independent t-tests and chi square were used to assess differences between females and males statistically. Results: 66 female (16.6%) and 331 male (83.4%) patients with gout (MSU crystals 60.6 vs 68.6%, respectively) were included. At baseline, females compared to males had a significantly higher age (73±12 vs 63±13 years, p<0.001), BMI (30.1±5.2 vs 28.7±4.7 kg/m 2, p=0.034) and diuretic use (63.6 vs 27.8%, p<0.001). Females had also a significantly higher percentage of comorbidities, including hypertension (77.3 vs 59.5%, p=0.003), diabetes (48.5 vs 22.7%, p<0.001) and chronic kidney disease (eGFR of 46.4±24.2 vs 62.5±22.9, p<0.001). There was no significantly difference in serum and urine uric acid concentration, current urate lowering and prophylactic medication, presence of tophi and nephrolithiasis. Also, the FEUa was similar in females vs males (5.1±3.0 vs 4.4%±1.7%, p=0.201). Conclusions: The clinical profile of gout in females significantly differs compared with males: significantly older, more advanced decrease in renal function and higher prevalence of hypertension in the females. As Dutch guidelines recommend starting with a diuretic for the treatment of hypertension in patients aged 70+; this may have a role in explaining the higher numbers of females using diuretics. The start of diuretics has previously been associated with hyperuricemia and increases the risk of gout in the female population. Although diuretic use has proven to be a safe and effective first-line treatment for hypertension, our results suggest that diuretic use in combination with a decreased renal function is associated with an increased risk at developing gout in females, and possibly needs reconsideration. Furthermore, despite the fact that the FEUa was similar distributed between genders, females did seem to have a lower urinary uric acid excretion. However, the number of patients with tophi and nephrolithiasis and the serum uric acid level are comparable between the genders. This suggests that the urate burden is similar but that the clinical profile for the development of gout differs due to the uric acid production vs excretion. In depth analysis of our population underlines the differences in female and male gout patients which highlight the need for more research into pathophysiology and management of gout between sexes. Disclosure of Interest: None declared